The evolving role of the orphan nuclear receptor ftz‐f1, a pair‐rule segmentation gene. Issue 6 (November 2013) - Heffer, Alison; Grubbs, Nathaniel; Mahaffey, James; Pick, Leslie
SUMMARY Segmentation is a critical developmental process that occurs by different mechanisms in diverse taxa. In insects, there are three common modes of embryogenesis—short‐, intermediate‐, and long‐germ development—which differ in the number of segments specified at the blastoderm stage. While genes involved in segmentation have been extensively studied in the long‐germ insect Drosophila melanogaster (Dm), it has been found that their expression and function in segmentation in short‐ and intermediate‐germ insects often differ. Drosophila ftz‐f1 encodes an orphan nuclear receptor that functions as a maternally expressed pair‐rule segmentation gene, responsible for the formation of alternate body segments during Drosophila embryogenesis. Here we investigated the expression and function of ftz‐f1 in the short‐germ beetle, Tribolium castaneum (Tc). We found that Tc‐ftz‐f1 is expressed in stripes in Tribolium embryos. These stripes overlap alternate Tc‐Engrailed (Tc‐En) stripes, indicative of a pair‐rule expression pattern. To test whether Tc‐ftz‐f1 has pair‐rule function, we utilized embryonic RNAi, injecting double‐stranded RNA corresponding to Tc‐ftz‐f1 coding or non‐coding regions into early Tribolium embryos. Knockdown of Tc‐ftz‐f1 produced pair‐rule segmentation defects, evidenced by loss of expression of alternate En stripes. In addition, a later role for Tc‐ftz‐f1 in cuticle formation was revealed. These results identify a new pair‐rule gene in Tribolium and suggest that its role in segmentation may be shared among holometabolous insects. Interestingly, while Tc‐ftz‐f1 is expressed in pair‐rule stripes, the gene is ubiquitously expressed in Drosophila embryos. Thus, the pair‐rule function of ftz‐f1 is conserved despite differences in expression patterns of ftz‐f1 genes in different lineages. This suggests that ftz‐f1 expression changed after the divergence of lineages leading to extant beetles and flies, likely due to differences in cis‐regulatory sequences. We propose that the dependence of Dm‐Ftz‐F1 on interaction with the homeodomain protein Ftz which is expressed in stripes in Drosophila, loosened constraints on Dm‐ftz‐f1 expression, allowing for ubiquitous expression of this pair‐rule gene in Drosophila.